Interrelations between Sport and Leisure Activities among High School Students - Szabo, Daniel; Kovács-Nagy, Klára; Müller, Anetta (Central European Journal of Educational Research, 2022)
Research on the education, upbringing and habits of high school students is extremely varied and diversified across all areas of education. In our case, we would like to investigate students’ sporting and leisure habits, as several studies have found possible breakpoints in students’ lifestyles during this period, which is particularly true for sporting habits. Our research focuses on the leisure habits of students learning in Nyíregyháza and Debrecen. We were looking for answers to the following questions: What is the most common form of leisure time activity among the students investigated? and, what social and sport-related variables are associated with differences in leisure time use? We conducted a questionnaire survey in secondary schools in the two cities (N=450) to answer our questions. The analyses showed that screentime activities continue to play a dominant role in the leisure time of the age group studied, followed only by activities that can be linked to active leisure.